1995
DOI: 10.1029/95jd01168
|View full text |Cite
|
Sign up to set email alerts
|

The 4‐day wave in the Antarctic mesosphere

Abstract: Abstract. A zonal wave number one eastward propagating planetary wave observed in the high latitude winter stratosphere with a period near 4 days has been studied by a number of previous authors. Radar observations coupled with stratospheric analyses are here used to demonstrate that this wave, known as the 4-day wave, extends into the Antarctic upper mesosphere. Previous workers have asserted that the wave is a manifestation of the observation of warm pools rotating in the polar vortex, and that the pool seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 21 publications
4
20
0
Order By: Relevance
“…These findings agree well with previous observations related to warm pools and their phase velocities (e.g. Lawrence et al, 1995). However, the phenomenon of a moving warm pool could also be interpreted as a structure in the temperature field moving with the background wind.…”
Section: Wave Activity In Wintersupporting
confidence: 90%
See 1 more Smart Citation
“…These findings agree well with previous observations related to warm pools and their phase velocities (e.g. Lawrence et al, 1995). However, the phenomenon of a moving warm pool could also be interpreted as a structure in the temperature field moving with the background wind.…”
Section: Wave Activity In Wintersupporting
confidence: 90%
“…Similar to the studies by Nozawa et al (2003b), the wave's amplitude was reported to maximize at lower altitudes (approximately 70 km) than the summer QTDW (85-88 km). Lawrence et al (1995) used radar observations together with stratospheric analyses to show that a four-day wave can reach to the Antarctic upper mesosphere. The study confirmed that the wave is associated with quasi-non-dispersive warm pools that rotate in the polar vortex.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works (Venne and Stanford, 1982;Lait and Stanford, 1988;Lawrence et al, 1995) have described the presence of waves in the Southern Hemisphere mesosphere and stratosphere with zonal wave numbers one to three and periods of 4, 1.8 and 1.2 days. This 4-day wave is an eastward propagating disturbance with a zonal wave number one.…”
Section: A Mechanism For the Observed Seasonal Behaviormentioning
confidence: 99%
“…The E1 5DW was also found in the meridional wind as a winter phenomenon using meteor radar wind measurements at the South Pole during 1995 by Palo et al (1998). Simulation using the extended Canadian Middle Atmosphere Model (CMAM) by McLandress et al (2006) predicted E1 quasi-4-day wave during austral winter between 63 and 85 • S, as observed by Lawrence et al (1995), Prata (1984) and Stanford (1979, 1982), although Hough function theory predicts that the quasi-4-day wave corresponds to (2, 1) (Hirota and Hirooka, 1984;Salby, 1984;Talaat et al, 2002). Discrepancies between our results and previous 5DW studies from groundbased radar measurements introduced above may also be a longitude variability caused by a mixture of these different wave modes.…”
Section: Discussionmentioning
confidence: 83%